KIDNEY FUNCTION AND SOME HEAVY METALS STATUS OF LEATHER TANNERS AT MAJEMA TANNERY, KOFAR WAMBAI, KANO STATE- NIGERIA. - Gadanya, A. M.; Maiwada, R. D.; Wudil, A. M.; Imam, A. A. (FUDMA JOURNAL OF SCIENCES, 2023)
Leather tanners are exposed to toxic chemicals and heavy metals that may be harmful to their health. The present study was aimed at assessing the effect of tanning processes on renal function and some heavy metals status of leather tanners at Majema Tannery Kofar Wambai, Kano. Sixty (60) apparently healthy male individuals were divided into four groups of 15 persons each (i.e control group obtained from Dorayi-Gwale Local Government, non - tanners residing near the tannery but do not participate in the work, moderate tanners with working experience of 0- 10 years and heavy tanners with working experience of 10 years and above). Some kidney function parameters in serum (urea, creatinine and electrolytes i.e Na, K+, Cl- and HCO3-), and in urine (albumin and creatinine), serum vitamin D and Lactate Dehydrogenase activities (using NAD as a substrate) were measured by spectrophotometric method. Serum levels of some heavy metals (chromium, cadmium and zinc) were measured using atomic absorption spectrometry. Systolic and diastolic blood pressures were measured using sphygmomanometer. There was significant increase in albuminuria in all the four groups and lactate dehydrogenase for the heavy tanners (p>0.05), while serum vitamin D was within normal range. Both heavy and moderate tanners had significantly (p<0.05) higher serum chromium and cadmium than control, and non-tanners. Systolic and diastolic blood pressures for all the four groups were within normal range. Thus, there is possibility of renal impairment, if not now, but in the near future for the tanners.